The geology and evaluation of the "A"-reef at No.3 shaft, Western Holdings Mine, Welkom goldfield - Blamey, Nigel John Frederick (Rhodes University, Faculty of Science, Department of Geology, 1992)
The "A" -Reef occurs within the Aandenk Formation of the Central Rand Group, Witwatersrand Supergroup, in the Welkom Goldfield. It comprises the Witpan and Uitsig Reefs which are both oligomictic conglomerates, and are exploited for their gold content by Anglo American Corporation. The main Witpan channel complex is orientated in a NW-SE direction and occurs close to No.3 Shaft of Western Holdings Mine where it is currently being mined. The Witpan Reef varies in thickness from 7-220cm, with lateral facies changes controlling the thickness. Within the reef, gold is associated with degradation surfaces, carbonaceous material, increase in pebble sphericity, and channel edges. Two channel edges have yielded the best gold values on No.3 Shaft although the potential for further payable gold lies in the recognition of sieve conditions. The potential also exists for extensions of the "carbon"-bearing Uitsig channel currently being mined on President Steyn Mine. The palaeo-environment proposed for formation of the Witpan Reef is a braidplain that was partly reworked by a brief transgression. Ore evaluation using geostatistics was considered a valid technique as the dataset is sufficiently well structured. Semi-variograms in the channel and across-channel directions differ markedly. It was found that variograms of gold in cmg/t lacked sufficient structure for modelling, however, log semi-variogram modelling followed by simple log-kriging and back-transformation, proved to be the most successful method. Owing to the morphology and distribution of gold within the reef, a geologically based geostatistical valuation method is proposed. The potential for further exploration of "A" -Reef depends on a substantially higher gold price. In this event, exploration of Uitsig Reef to the southwest of the current mining area is recommended as well as a new exploration strategy for Witpan Reef.
Keywords: Gold mines and mining -- South Africa -- Free State; Gold ores -- Geology -- South Africa